Impact of covid -19 among smokers in Oman - A. Sathakathulla, A.; G. Fajlul Kareem, M. (SPC Journal of Social Sciences, 2021)
This study will revolve around recent tobacco-users during this pandemic Covid-19 scenario and threat to the smokers. The young smokers are increasing day by day exponentially around the world and a big challenge to parents and governments. In Oman, the number of smokers and tobacco sales is increasing rapidly year by year. This pandemic situation hurdled the movement worldwide; Covid-19 is a big threat to the community with high risk for infected people with comorbidity. As per WHO guidelines the smokers have high risk of Covid-19 infection with high mortality chances. This study reveals around the impact of Covid-19 among tobacco users in Oman during this pandemic.Â Â